2019
DOI: 10.1038/s41598-019-55455-6
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Implications of Sub-grouping HER2 Positive Tumors by Amplicon Structure and Co-amplified Genes

Abstract: ERBB2 amplification is a prognostic marker for aggressive tumors and a predictive marker for prolonged survival following treatment with HER2 inhibitors. We attempt to sub-group HER2+ tumors based on amplicon structures and co-amplified genes. We examined five HER2+ cell lines, three HER2+ xenographs and 57 HER2+ tumor tissues. ERBB2 amplification was analyzed using digital droplet PCR and low coverage whole genome sequencing. In some HER2+ tumors PPM1D, that encodes WIP1, is co-amplified. Cell lines were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Myc is a transcription factor that regulates cell proliferation ( 33 ). Moreover, Myc is widely expressed during embryogenesis, but also in highly proliferative adult tissues, such as the epidermis and gut ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Myc is a transcription factor that regulates cell proliferation ( 33 ). Moreover, Myc is widely expressed during embryogenesis, but also in highly proliferative adult tissues, such as the epidermis and gut ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aside GSDMs, there are other frequently amplified genes near the HER2 amplicon that could affect HER2 BC clinical behavior, such as TOP2A (in 17q21.2 [ 192 ]) or genes within the 17q23 amplicon such as RPS6KB1 , PPM1D , or MIR21 [ 193 , 194 ]. PPM1D (located at the 17q23 region) encodes the wildtype p53-induced phosphatase1 (WIP1), a protein that negatively regulates p53 function, enhances cell cycle progression, and accelerates tumor incidence in HER2 BC mouse models [ 195 ].…”
Section: Strategies In Pre-clinical Developmentmentioning
confidence: 99%
“…PPM1D (located at the 17q23 region) encodes the wildtype p53-induced phosphatase1 (WIP1), a protein that negatively regulates p53 function, enhances cell cycle progression, and accelerates tumor incidence in HER2 BC mouse models [ 195 ]. In HER2/WIP1-amplified tumors, pharmacological WIP1 inhibition reduced cell proliferation and, importantly, also partially restored sensitivity to trastuzumab [ 193 , 194 ], thus suggesting that the WIP1 oncogene could be another potential therapeutic target to reverse anti-HER2 therapy resistance.…”
Section: Strategies In Pre-clinical Developmentmentioning
confidence: 99%
“…ErbB2 has also been incorporated in CARengineered NK-92 cells to be evaluated in cancer experiments [153]. It was found that ErbB2 is overexpressed in some types of human tumors with an epithelial origin and it is thought that it has a role in cancer development and progression [4,154]. Several CAR-engineering approaches capable of targeting the ErbB2-positive cancers are now in development process.…”
Section: Preclinical Studies On Solid Tumorsmentioning
confidence: 99%
“…Cancer immunotherapy exploits the body’s immune system to fight against cancer and is classified by three branches: immune checkpoint inhibitors (ICIs), adoptive cell therapies (ACTs), and tumor vaccines [ 2 , 3 ]. Cancer immunotherapy can help patients with advanced tumors or recurrent cancers [ 4 ].…”
Section: Introductionmentioning
confidence: 99%